2016
DOI: 10.1038/ncomms10535
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical camera chip for simultaneous imaging of multiple metabolites in biofilms

Abstract: Monitoring spatial distribution of metabolites in multicellular structures can enhance understanding of the biochemical processes and regulation involved in cellular community development. Here we report on an electrochemical camera chip capable of simultaneous spatial imaging of multiple redox-active phenazine metabolites produced by Pseudomonas aeruginosa PA14 colony biofilms. The chip features an 8 mm × 8 mm array of 1,824 electrodes multiplexed to 38 parallel output channels. Using this chip, we demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(91 citation statements)
references
References 45 publications
1
88
2
Order By: Relevance
“…S9C), possibly due to degradation or modification during the prolonged agar extraction protocol. Thus, we sought to demonstrate a role for MexGHIOpmD in 5-Me-PCA release from colonies by using an integrated circuit (IC) chip, an electrochemical metabolite sensing platform recently developed by our group (48,54). This technique enables direct detection of phenazines as they are released from the biofilm using the same SWV-based electrochemical detection modality described earlier, eliminating the need for agar processing and extraction steps that may allow conversion of 5-Me-PCA to other derivatives before HPLC analysis (SI Appendix, Fig.…”
Section: Mexghi-opmd Contributes To Fitness In Shaken Liquid Culturesmentioning
confidence: 99%
“…S9C), possibly due to degradation or modification during the prolonged agar extraction protocol. Thus, we sought to demonstrate a role for MexGHIOpmD in 5-Me-PCA release from colonies by using an integrated circuit (IC) chip, an electrochemical metabolite sensing platform recently developed by our group (48,54). This technique enables direct detection of phenazines as they are released from the biofilm using the same SWV-based electrochemical detection modality described earlier, eliminating the need for agar processing and extraction steps that may allow conversion of 5-Me-PCA to other derivatives before HPLC analysis (SI Appendix, Fig.…”
Section: Mexghi-opmd Contributes To Fitness In Shaken Liquid Culturesmentioning
confidence: 99%
“…PCA and other phenazines facilitate extracellular anaerobic respiration (Rabaey et al ., ; Wang et al ., ; Glasser et al ., ). Moreover, phenazine biosynthesis is regulated by quorum sensing (Pierson et al ., ; Khan et al ., ; O'Loughlin et al ., ) and oxygen (O 2 ) status (Bellin et al ., ). These findings indicate that phenazines play a role in community‐regulated respiration.…”
Section: Introductionmentioning
confidence: 99%
“…Although only pyocyanin is exclusively produced by PA, the simultaneous detection of several metabolites is advantageous both for bacterial research purposes, but also for using the presence of the compounds as a molecular signature for PA. Several studies have conducted multiple molecule detection using electrochemical measurements. These studies have mapped the potential values belonging to the aforementioned metabolites and do not overlap, which allows the simultaneous detection of the compounds in one measurement, e.g., through DPV or SWV in the relative potential range of −0.7 to 1.5 V [ 35 , 41 , 48 , 49 , 50 , 51 , 52 ].…”
Section: Electrochemical Detection Of Pyocyaninmentioning
confidence: 99%
“…Another study demonstrated the simultaneous electrochemical measuring and imaging of pyocyanin and other metabolites in biofilms using an SECM coupled to an electrochemical camera chip. This approach gives a unique resolution of the electrochemical activity of biofilms [ 50 ]. It is worth noticing that in the SECM setups, redox mediators have been used to generate a feedback approach curve.…”
Section: Electrochemical Detection Of Pyocyaninmentioning
confidence: 99%